Pengaruh Arah Datang Cahaya Matahari terhadap Kinerja Sistem Photovoltaic - Nur Rohman; Rifky; Ariyansah, Riyan; M. Shofriyan Efendi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2024)
Building as a source of energy is not something extraordinary, as in BIPV (building-integrated photovoltaic) technology. Likewise, making buildings a NZEB (net zero energy building) has become a necessity in the context of saving energy use. One energy converter that has been used in buildings is PLTS or solar cells, which is a power plant that converts solar radiation into electrical energy (photovoltaic system). The conversion process is influenced by the direction of sunlight coming to the position of the solar cells that are placed on the roof of the building. This study aims to determine the effect of the direction of sunlight on the performance of solar cells, so that it is obtained from the right direction of sunlight. Solar cells are exposed to the north, east and west. The input parameters for each direction are the intensity of solar radiation, air humidity, wind speed, air temperature, upper side temperature and lower side temperature of the solar cell. Meanwhile, the resulting output parameters are electric voltage and electric current. The results showed that the north direction without cooling produced a total output power of 666.59 W and an average efficiency of 13.54%, for those using the cooler produced a total output power of 737.71 W and an average efficiency of 14.16%. East direction produces a total output power of 454.81 W and an average efficiency of 11.51%, for those using the cooling system it produces a total output power of 542.25 W and an average efficiency of 13.90%. West direction produces a total output power of 340.33 W and an average efficiency of 13.22% for those using a cooling system resulting in a total output power of 550.72 W and an average efficiency of 13.29%. The highest performance of solar cells is obtained from solar cells that are placed towards the North using a cooler where the total output power is 737.71 W and an average efficiency of 14.16%, and for without a cooling system the total output power is 666.59 W and the average efficiency is 13.54%.